Dissolving Polymer Microneedles for Transdermal Delivery of Insulin - Zhang, Na; Zhou, Xinxin; Liu, Libo; Zhao, Lini; Xie, Hui; Yang, Zhihang (Frontiers in Pharmacology, 2021)
It’s of great significance to develop insulin-loaded dissolving microneedles (MNs) which are fabricated with various methods and materials for transdermal delivery of insulin to effectively and efficiently treat diabetes. In this work, we present a kind of FITC-insulin tip-loaded dissolving MNs fabricated with the mixture of polyvinyl alcohol (PVA) and sucrose using homemade PDMS MNs mold under vacuum condition. The uniform appearance of MN arrays contributes to controlling the drug dosage well as required. Sufficient mechanical strength for penetrating tough stratum corneum can be obtained by vacuum frozen-drying for at least 6 h after peeling MNs off the mold. About 90% of the FITC-insulin localized in the conical MN tips and can be released into skin within 2 min after insertion. To evaluate the absorption rate of equal 0.1 U of FITC-insulin delivered from shallow subcutaneous tissue into deep systemic circulation, the In Vivo Imaging System (IVIS) was used to determine the relative drug content of FITC-insulin residual on the skin surface. And 0.1 U of FITC-insulin in the injection solution was absorbed completely within 2 h, which was faster than that loaded in the MNs within 3 h. Even so, the total hypoglycemic effect of insulin was not affected largely by this delicate difference between the absorption rate. These results suggested that the efficient MN fabrication process proposed in this work show great potential for mass production and practical application of drug-loaded dissolving MNs in future.